2013
DOI: 10.1080/1331677x.2013.11517625
|View full text |Cite
|
Sign up to set email alerts
|

Off-Balance Sheet Activities Impact on Commercial Banks Performance: An Emerging Market Perspective

Abstract: This paper examines the effect of off-balance sheet (OBS) activities on performance of the banks listed on Istanbul Stock Exchange (ISE). We use four measures of performance including bank's risk exposures, profitability, leverage, and liquidity position. We find that both bank-specific risk and foreign exchange rate risk are positively related with OBS activities. This indicates that OBS activities increase bank-specific and foreign exchange risk exposures of the banks in Turkey. The positive relationship mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The profit per unit risk of banks declines with the increase in their OBS activities. Aktan et al (2013) examine the effect of OBS activities on performance of the banks listed on the Istanbul Stock Exchange and reveal that both bank-specific and foreign exchange rate risks are positively related with OBS activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The profit per unit risk of banks declines with the increase in their OBS activities. Aktan et al (2013) examine the effect of OBS activities on performance of the banks listed on the Istanbul Stock Exchange and reveal that both bank-specific and foreign exchange rate risks are positively related with OBS activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Ahmad and Ariff (2007) the ratio of the aggregated OBS activities to aggregated total assets in Eastern Europe, South and Central America, Africa and Far East and Central Asia equals 15%, 12%, 18%, 12% in 2005, respectively, compared to 60%, 63%, 41% for North America, NAFTA, and G7 countries, respectively. Similarly, studies carried out by Aktan et al (2013) on Turkey, Pushkala et al (2017) on India, and Ahmad and Misman (2012) in Malaysia in their findings they reported that the OBSA are showing an increasing trend. As part of the world financial system, there has been a shift in the sources of income of the South Asian commercial banks.…”
Section: Why Banks Engage In Obsamentioning
confidence: 68%
“…Most research on off-balance sheet activities has been dominated by studies conducted in developed countries such as the USA and Europe. Even the wave of studies (Ahmad and Misman, 2012;Aktan et al, 2013; is carried out on the emerging economies and in the authors have argued that the financial structure, institutional and legal environment of developed and developing countries are not comparable. It is, therefore, a critical contemporary issue in financial and regulatory institutions and markets to understand the factors which affect the OBS decision in commercial banks in Pakistan, India, and Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it has been widely used in estimating total-factor efficiencies [8,9].Although banks can generate more revenue through innovative products [2], it is noted that different from other industries' innovation, financial product innovation also creates potential risks for bank operations. Calmès and Théoret [10], Aktan et al [11] analyzed the statistics of commercial banks in Canada and Istanbul, respectively, and found that the growth of the innovative products may lead to an increase of risks for commercial banks. Therefore, it is of great significance to consider the impact of product innovation risks when analyzing the performance of commercial banks' product innovation.…”
mentioning
confidence: 99%